(untitled) (Community Based Medical Journal, 2024)
A cross-sectional study was done to evaluate computed tomography (CT) scans as a diagnostic tool for distinguishing between benign and malignant gallbladder masses corroborated by histopathological findings. The study was conducted in the Department of Radiology & Imaging of Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh, between January and December of 2013. The study included a total of 45 patients who were ultrasonographically diagnosed with gallbladder masses. Later, those patients underwent CT scans using a 16-slice helical CT scan machine. All CT scan findings were interpreted by the specialist radiologists, focusing on lesion involvement, contrast enhancement characteristics, and invasion into adjacent structures. Postoperative tissues were examined histopathologically, and these findings were correlated with the CT scan results. The study revealed a higher prevalence of GBC in females (73.33%) and in the age group of 40-60 years. CT scans indicated malignancy in 84.44% of cases, which was confirmed as adenocarcinoma in 88.89% of cases through histopathology. The sensitivity, specificity, and accuracy of CT scans for detecting malignant gallbladder masses were 90.24%, 75.00%, and 88.89%, respectively. For benign masses, the corresponding values were 75.00%, 90.24%, and 88.89%. The positive predictive value was notably high at 97.37% for malignant masses but lower at 42.86% for benign masses. CT scans demonstrated high sensitivity and specificity in the diagnosis of malignant gallbladder masses, corroborated by histopathological findings. The study underscores the utility of CT scans as an effective, non-invasive diagnostic tool for early detection and management of gallbladder masses, although caution is advised in interpreting benign results due to a lower positive predictive value. CBMJ 2024 January: vol. 13 no. 01 P: 22-27